2017
DOI: 10.1261/rna.062158.117
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ region of Xist RNA has the potential to associate with chromatin through the A-repeat

Abstract: X inactive-specific transcript () is a long noncoding RNA that plays an essential role in X chromosome inactivation. Although RNA, like common protein-coding mRNAs, is transcribed by RNA polymerase II, spliced and polyadenylated, it is retained in the nucleus and associates with the X chromosome it originates from. It has been assumed that RNA recruits proteins involved in epigenetic modifications and chromatin compaction to the X chromosome. One of the major proteins constituting the nuclear matrix, hnRNP U, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Using Tiling CRISPR, we successfully identified the known Xist silencing domain, A-repeats. A-repeats reportedly mediate silencing through multiple mechanisms: interacting with silencing factors 2,35 , recruiting genes into a Xist-mediated silencing compartment 36 , regulating Xist spreading 37,38 , or regulating Xist splicing 39 . However, our findings suggest a novel function whereby A-repeats positively regulate Xist transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Using Tiling CRISPR, we successfully identified the known Xist silencing domain, A-repeats. A-repeats reportedly mediate silencing through multiple mechanisms: interacting with silencing factors 2,35 , recruiting genes into a Xist-mediated silencing compartment 36 , regulating Xist spreading 37,38 , or regulating Xist splicing 39 . However, our findings suggest a novel function whereby A-repeats positively regulate Xist transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which Repeat-A promotes Xist stability are unclear. Lastly, in transgenic Xist cDNA overexpression experiments, Repeat-A appears to be involved in targeting Xist to actively transcribed regions (27,28). How Repeat-A is involved in this targeting is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of Tsix expression is beyond the scope of this review, and more specific details can be found in references ( Willard, 1996 ; Gontan et al, 2012 ; Gayen et al, 2015 ). Once Xist expression has been activated, Xist binds Polycomb repressive complex 2 (PRC2) via Repeat A formed Xist-PRC2 complex, and YY1 tethers the PRC2-Xist complex through Repeat C to the Xi nucleation center which obtains lncRNA Xist-PRC2 complex by the RNA polymerase II (RNA Pol II) ( Jeon and Lee, 2011 ; Thorvaldsen et al, 2011 ; Makhlouf et al, 2014 ; Chigi et al, 2017 ).…”
Section: The Role Of Lncrna Xist In X Chromosome Dosage Compensationmentioning
confidence: 99%